Transitional Justice and Sustainable Peace: Comparative Insights and Policy Implications - Hermansyah (Legalis : Journal of Law Review, 2025)
Transitional justice plays a pivotal role in restoring peace and accountability in societies emerging from conflict. This narrative review explores the mechanisms employed across various post-conflict settings, aiming to understand their effectiveness and contextual relevance. Using systematic literature search methods across databases such as Scopus, Web of Science, and Google Scholar, the review analyzed peer-reviewed articles, research reports, and gray literature published within the last decade. Boolean search strategies and specific inclusion criteria were applied to identify studies focused on formal legal structures, community-based practices, gendered experiences, economic reparations, environmental considerations, and cross-national comparisons. The findings reveal that while international tribunals contribute to legal precedent, their detachment from local realities often limits community impact. Truth and Reconciliation Commissions (TRCs) have helped articulate historical grievances, but their effectiveness depends heavily on political will and institutional support. Informal mechanisms rooted in local culture offer promising pathways for healing and legitimacy, especially when integrated with civil society participation. Gender-sensitive approaches enhance justice outcomes by addressing violence against women and ensuring female representation. Furthermore, economic and environmental justice are increasingly recognized as integral to sustainable post-conflict recovery. Comparative cases from Timor Leste, Guatemala, and Bosnia highlight the importance of local engagement and context-specific adaptation of global frameworks. This study emphasizes the urgency of systemic reforms, inclusive policy-making, and long-term investments in justice mechanisms. It advocates for further research to overcome methodological challenges and supports multi-level strategies that center on community empowerment and resilience.